HORIZONTAL DEPOSIT IDENTIFICATION AND VERTICAL CLIFF EFFECT TO 2-D RESISTIVITY SURVEY WITH WENNER CONFIGURATION (CASE STUDY OF JEPANG CAVE, BANDUNG) - KURNIAWAN (NIM : 22107020), BUDI
The research was carried out at Jepang Cave which is located in Taman Hutan Raya Ir. H. Juanda Bandung, West Java Province. The cave is subsurface opened hole which is considered similar to sill. The research aim to know the resistivity anomaly pattern for the cavity subsurface, to analyze the accuracy of 2-D resistivity survey with Wenner configuration when it was applied to identify cave which close to cliff. The field survey measurement was carried out in 3 survey lines with different distance from the vertical cliff. Line 1, line 2, and line 3 locations has distance about 8 meter, 23 meter, and 65 meter from cliff respectively. 2-D Wenner configuration resistivity survey obtained the apparent resistivity from the field measurement and the true resistivity values is generated from Res2DInv software model. The resistivity values become smaller when the survey line distance from vertical cliff progressively far. The comparison between actual position and model anomaly of the horizontal deposit show that the survey line with electrode spacing of 5 meter has better interpretation than the electrode spacing of 10 meter, although line 2 and line 3 with the electrode spacing of 5 meter has same RMS error of 4.2 % which is greater than spacing of 10 meter with values of 1.7 % and 1.2 %. The line 1 with spacing of 5 meter has RMS error value of 2 % and for spacing of 10 meter about 2.2 %. From the resistivity interpretation value, the result does not represent the real position and dimension of deposit, due to the close distance between the caves.